2011
DOI: 10.1029/2011gl049004
|View full text |Cite
|
Sign up to set email alerts
|

Karakoram glacier surge dynamics

Abstract: [1] We examine the surges of five glaciers in the Pakistan Karakoram using satellite remote sensing to investigate the dynamic nature of surges in this region and how they may be affected by climate. Surface velocity maps derived by feature-tracking quantify the surge development spatially in relation to the terminus position, and temporally with reference to seasonal weather. We find that the season of surge initiation varies, that each surge develops gradually over several years, and that maximum velocities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 29 publications
19
185
2
Order By: Relevance
“…This allowed a faster computational approach (because ice ablation is calculated in each belt, rather than in each single 30-m cell of the ASTER GDEM, or in each 90-m cell of the SRTM DEM), while still providing an acceptable depiction of ice ablation. is 83 m yr 21 , while velocity from Quincey et al (2011) in the same altitude range (3700-4600) averages 90 m yr 21 , and the one from the model is 89 m yr 21 . Therefore, we assume that our model depicts ice flow reasonably well, for the sole purpose of carrying out a hydrological budget of the catchment.…”
Section: A Ice Ablation and Flowmentioning
confidence: 96%
See 1 more Smart Citation
“…This allowed a faster computational approach (because ice ablation is calculated in each belt, rather than in each single 30-m cell of the ASTER GDEM, or in each 90-m cell of the SRTM DEM), while still providing an acceptable depiction of ice ablation. is 83 m yr 21 , while velocity from Quincey et al (2011) in the same altitude range (3700-4600) averages 90 m yr 21 , and the one from the model is 89 m yr 21 . Therefore, we assume that our model depicts ice flow reasonably well, for the sole purpose of carrying out a hydrological budget of the catchment.…”
Section: A Ice Ablation and Flowmentioning
confidence: 96%
“…Specifically, the model uses a simplified ice flow approach, by shifting a proper quantity of ice from an altitude belt to the lower one. The large valley glaciers in the Karakoram flow with maximum speeds of about 100-150 m yr 21 , while the glacier tongues are on the order of 20-40 km long (e.g., Mayer et al 2006;Quincey et al 2011). Simulations of glacier runoff with periods of 50-100 years lead to an ice movement of 5-15 km, that is, less than half of the glacier tongue length.…”
Section: The Glaciohydrological Modelmentioning
confidence: 99%
“…• In other research, "more than 50% of Karakoram glaciers were advancing or stable between " (Scherler et al, 2011, and Fuita and Nuimura (2011) reported a descending trend in the modeled equilibrium-line altitude in the Karakoram during 1976 reported an increase in winter precipitation since 1961, a potential source for greater accumulation in the upper parts of glaciers Quincey et al 2009Quincey et al , 2011. Between 1961 and 2000, Fowler and Archer report, mean summer temperature declined at all climate stations in the region, probably resulting in a decreasing glacier melt.…”
Section: Other Researchmentioning
confidence: 99%
“…Moreover, individual glacier advances in eastern Karakoram have also been reported in the Shyok valley during the last decade (Raina and Srivastva, 2008). These individual advances and mass gain episodes could be attributed to surging (Barrand and Murray, 2006;Hewitt, 2011;Copland et al, 2011;Quincey et al, 2011), winter temperature decrease (Shekhar et al, 2010) and increased solid precipitation in the accumulation areas (Fowler and Archer, 2006). Copland et al (2011) reported an increase of glacier surge activities after 1990 in the western and central Karakoram region.…”
Section: Introductionmentioning
confidence: 99%